2023
DOI: 10.1111/aor.14541
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal life support in mitral papillary muscle rupture: Outcome of multicenter study

Abstract: BackgroundPost‐acute myocardial infarction papillary muscle rupture (post‐AMI PMR) may present variable clinical scenarios and degree of emergency due to result of cardiogenic shock. Veno‐arterial extracorporeal life support (V‐A ECLS) has been proposed to improve extremely poor pre‐ or postoperative conditions. Information in this respect is scarce.MethodsFrom the CAUTION (meChanical complicAtion of acUte myocardial infarcTion: an InternatiOnal multiceNter cohort study) database (16 different Centers, data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Acute MR secondary to PMR is a rare mechanical complication of acute MI with an incidence of 0.05–0.26% [ 1 ]. The definite treatment remains emergency mitral surgery with a high operative mortality (24–39%) [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute MR secondary to PMR is a rare mechanical complication of acute MI with an incidence of 0.05–0.26% [ 1 ]. The definite treatment remains emergency mitral surgery with a high operative mortality (24–39%) [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The largest study on the use of VA ECMO in PMR was a retrospective analysis of multicenter registry (the CAUTION study) [ 1 ]. The authors reported on 23 patients that required VA ECMO support (with 43.5% of patients requiring it preoperatively).…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular free wall rupture (LVFWR), ventricular septal rupture (VSR), and papillary muscle rupture (PMR) after acute myocardial infarction (AMI) are potentially fatal pathologies. Cardiac surgery for these mechanical complications of AMI has a high in-hospital mortality rate, which has not improved significantly over time [1][2][3]. Left ventricular (LV) unloading is essential to avoid excessive tension on the repair site after emergency surgery, which leads to burdensome hemostasis of the LV wall, a residual leak, patch dehiscence, and recurrence of LVFWR and VSR.…”
Section: Introductionmentioning
confidence: 99%